Perdas de água e solo na fase de implantação de sistemas de integração lavoura floresta e cultivos agricolas sob chuva natural na região de transição Cerrado/Amazônia - Rieger, Fernando Alexandre (2014)
The soil erosion is one of main drivers of soil degradation in Brazil, and it has causing great economic and environmental impacts. The increasing pressure on natural resources, such as water and soil, due to the expansion of agriculture and livestock for food, fiber and energy production, poses a great challenge to be managed in the context of sustainable development. In this regard, it is compelling the need for techniques that enables the sustainable use of water and soil, respecting their quantity and quality limitations. In this context, the integrated systems, as crop, livestock and forest integration (ILPF), as well as additional practices/systems that favor the maintenance of soil cover, are an important possibility to achieve the sustainable use of water and soil. The aim of this work was to study the water and soil losses under natural rainfall in different land use and cover settings. The research was carried out in the experimental field of Embrapa Agrosilvopastoral, in Sinop, state of Mato Grosso. The climate of the region is classified as Aw, according to Köppen, with average temperature and rainfall of 24,7 °C and 1.974 mm ano-1, respectively. The soil in the experimental area is classified as a dystrophic red yellow heavy clay Latosol, presenting plain to soft undulated relief (0 to 8 %). The treatments comprised six experimental plots under different land use and cover, respectively a perennial pasture, crop and forestry integrated system (ILF), eucalyptus plantation, soybean-corn crop in succession cropping, bare soil and forest. The plot size is 22 m long and 6m wide (132 m2), bounded by galvanized sheets of 3.00 x 0.30 m, inserted 0.15 m into the soil. In the lower end of the plots were placed a collecting trough that leads the runoff, through a PVC pipe, to tanks. The total rainfall during the study period was 1.997,1 mm, respectively 384,2 mm in 2012 and 1.613 mm in 2013, with concentrating period from January to March 2013. The same occurs with rainfall erosivity that presented the highest values during the months with high precipitation, ranging from 2.789 in January, 3.009 in February and 3.625 MJ mm ha- 1 h- 1 in March, with mean annual rainfall erosivity of 16.092 MJ mm ha- 1 h- 1 year- 1. The water losses ranged from 10,3 to 675,3mm, which represented 0,5 and 33,8 % of the total rainfall during the study period, respectively for treatments under forest and bare soil. The water loss in the treatment under bare soil was, on average, 94 % higher than the others, which demonstrates the effect of vegetation in reducing runoff. Soil losses in the evaluated treatments were below the average tolerance limits, except for the treatment under bare soil, where it was found that soil loss was 1,5 times higher than the average tolerance limits.